The use of computed tomography and scanning microscopy methods for assessing the alkaline reactivity of aggregate - Zapała-Sławeta, Justyna (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
The reaction of alkalis with aggregate containing reactive forms of silica (ASR) plays a significant role in shaping the durability of concrete, as the strongly hygroscopic reaction products generated lead to internal stress, causing its expansion and cracking. This study presents an extended analysis of corrosive processes occurring in mortars with reactive natural aggregate from Poland, using computed tomography and scanning microscopy methods. Numerous cracks in the grains and the surrounding cementitious matrix were observed, indicating a high degree of advancement of corrosive processes. Over time, the proportion of pores with reduced sphericity increased, indicating ongoing degradation of the mortars. The usefulness of computed tomography in studying the progress of ASR was demonstrated. Scanning microscopy confirmed that the cause of mortar degradation is the formed ASR gel with a typical composition, located within the volume of reactive grains, cracks propagating into the cementitious matrix, and accumulated in air voids.